Dextromethorphan Attenuates LPS‐Induced Adhesion Molecule Expression in Human Endothelial Cells. (15th February 2013) - Jiang, Shinn‐Jong; Hsu, Sheng‐Yao; Deng, Chuan‐Rou; Huang, Huey‐Chun; Liu, Shu‐Lin; Shi, Guey‐Yueh; Wu, Hua‐Lin
Abstract Objective This study examines the effect of Dextromethorphan (d‐3‐methoxy‐17‐methylmorphinan; DXM), a commonly used cough‐suppressing drug, on the expression of VCAM‐1 and ICAM‐1 in human umbilical vein endothelial cells (HUVECs) stimulated with lipopolysaccharide (LPS). Methods The effect of DXM on expression of cell adhesion molecules induced by LPS was evaluated by monocyte bindings in vitro and ex vivo and transmigration assays. The signaling pathways involved in the inflammation inhibitory effect of DXM were analyzed by Western blot and immunofluorescent stain. Results Pretreatment of HUVECs with DXM inhibited LPS‐induced adhesion of THP‐1 cells in vitro and ex vivo, and reduced transendothelial migration of these cells. Furthermore, treatment of HUVECs with DXM can significantly decrease LPS‐induced expression of ICAM‐1 and VCAM‐1. DXM abrogated LPS‐induced phosphorylation of ERK and Akt. The translocation of early growth response gene‐1 (Egr‐1), a downstream transcription factor involved in the mitogen‐activated kinase (MEK)‐ERK signaling pathway, was suppressed by DXM treatment. Furthermore, DXM inhibited LPS‐induced IκBα degradation and nuclear translocation of p65. Conclusions Dextromethorphan inhibits the adhesive capacity of HUVECs by reducing the LPS‐induced ICAM‐1 and VCAM‐1 expression via the suppression of the ERK, Akt, and NF‐κB signaling pathways. Thus, DXM is a potential anti‐inflammatory therapeutic that may modulate atherogenesis.